Molecular Mechanisms of Clonorchis sinensis-Host Interactions and Implications for Vaccine Development - Koda, Stephane; Zhu, Xing-Quan; Zheng, Kui-Yang; Yan, Chao (Frontiers in Cell and Developmental Biology, 2022)
Infections caused by Clonorchis sinensis remain a fundamental public health challenge for both humans and animals, causing pyogenic cholangitis, cholelithiasis, cholecystitis, biliary fibrosis, and even cholangiocarcinoma. However, the strategies used by the parasite as well as the immunological mechanisms put in place by the host have not yet been fully understood. With the advances in technologies and the accumulated knowledge of host-worm interactions, many vaccine candidates against liver flukes have been investigated using different strategies. In this review, we will explore and analyze in-depth the immunological mechanisms involved in the pathogenicity of C. sinensis. We will also highlight the different mechanisms by which the parasite interacts with its host. All these data put together will allow us to have a better understanding of the elements to be considered in the development of an effective vaccine against C. sinensis.